Assessment of Spontaneous Retinal Arterial Pulsations in Acute Central Retinal Vein Occlusions. (9th June 2020) - Arej, Nicolas; Vasseur, Vivien; Jabbour, Elyse; Manassero, Anthony; Giraud, Céline; Bruneau, Sébastien; Le Mer, Yannick; Mauget-Faÿsse, Martine
Abstract : Central retinal vein occlusion (CRVO) is a common retinal disease. Recent works mentioned spontaneous retinal arterial pulsations (SRAPs) as a feature of some CRVOs. This is a retrospective study on patients presenting with CRVO who were followed up for at least 6 months. The objective was to identify SRAP in the acute phase of the disease and determine their relationship with patients' characteristics and visual prognosis. A 10-second infrared film centered on the optic disc was recorded within a month of the onset of symptoms, and SRAPs were detected in two-thirds of the cases. Patients with SRAP were significantly younger than those without SRAP. Mean central macular thickness was significantly higher in the absence of SRAP, which was translated into a more severe macular edema; however, this difference faded with time. BCVA tended to be higher in the presence of SRAP at the 6-month follow-up when adjusted to baseline. This study demonstrates that SRAPs are a frequent finding, easily detected by infrared fundus video recording, and associated with a younger age and lesser macular edema.